Male–female differences in the association between incident hip fracture and proximal femoral strength: A finite element analysis study - Keyak, J.H.; Sigurdsson, S.; Karlsdottir, G.; Oskarsdottir, D.; Sigmarsdottir, A.; Zhao, S.; Kornak, J.; Harris, T.B.; Sigurdsson, G.; Jonsson, B.Y.; Siggeirsdottir, K.; Eiriksdottir, G.; et al. (Bone (New York, N.Y.), 2011)
Hip fracture risk is usually evaluated using dual energy X-ray absorptiometry (DXA) or quantitative computed tomography (QCT) which provide surrogate measures for proximal femoral strength. However, proximal femoral strength can best be estimated explicitly by combining QCT with finite element (FE) analysis. To evaluate this technique for predicting hip fracture in older men and women, we performed a nested age- and sex-matched case–control study in the Age Gene/Environment Susceptibility (AGES) Reykjavik cohort. Baseline (pre-fracture) QCT scans of 5500 subjects were obtained. During 4–7 years follow-up, 51 men and 77 women sustained hip fractures. Ninety-seven men and 152 women were randomly selected as age- and sex-matched controls. FE-strength of the left hip of each subject for stance (F Stance) and posterolateral fall (F Fall) loading, and total femur areal bone mineral density (aBMD) were computed from the QCT data. F Stance and F Fall in incident hip fracture subjects were 13%–25% less than in control subjects (p ≤ 0.006) after controlling for demographic parameters. The difference between FE strengths of fracture and control subjects was disproportionately greater in men (stance, 22%; fall, 25%) than in women (stance, 13%; fall, 18%) (p ≤ 0.033), considering that F Stance and F Fall in fracture subjects were greater in men than in women (p < 0.001). For men, F Stance was associated with hip fracture after accounting for aBMD (p = 0.013). These data indicate that F Stance provides information about fracture risk that is beyond that provided by aBMD (p = 0.013). These findings support further exploration of possible sex differences in the predictors of hip fracture and of sex-specific strategies for using FE analysis to manage osteoporosis. ► We performed a prospective study of hip fracture in a group of older men and women. ► Finite element-computed hip strength in fracture and control subjects was obtained. ► Men and women with fractures had lower hip bone strength than control subjects. ► The reduction in strength due to fracture was greater in men than in women. ► Further study of sex-differences in hip strength and fracture risk is warranted.